Existence of Day-of-the-Week Effect in Returns of Some Selected Indices of the Indian Stock Market - Kothari, Hem Chandra; Singh, Praveen; Patra, Sidheswar (Indian Journal of Research in Capital Markets, 2017)
The present study attempted to measure day-of-the-week effect on the returns and volatility of Bombay Stock Exchange (BSE) and National Stock Exchange (NSE) indices for the period from 2005 through 2014. Along with the descriptive statistics, t-test and ANOVA were used to capture mean deference in returns for the trading days Monday through Friday. Mean returns of only one index, Nifty Junior, were found statistically significant while using t-test ; whereas, no such difference was observed in any of the index (BSE and NSE) in ANOVA. To confirm the findings of t-test and ANOVA, an econometric model AR (1)-GARCH (1, 1) was used. In contrast to the findings of the other indices, returns on Monday for BSE small cap were found to be statistically significant. It was also observed that volatility on Monday for returns on BSE small cap were statistically significant. Returns on Tuesday, for BSE small cap and BSE mid cap, were found to be negative and statistically significant. Returns on these two indices were also found to be negatively volatile on Tuesday. Wednesday effect was only observed for Nifty Junior, but no volatility was captured on Wednesday for Nifty Junior. Returns on Nifty Junior were also found to be positive and statistically significant on Friday, but volatility was captured for returns on Nifty Junior on Friday.